The Influence of Trust on Privacy Decisions - An Exploratory Study in the Context of the Metaverse - Dennler, Johanna (My University, 2025)
The pervasive data collection in digital environments makes understanding user privacy decisions critical. While trust is a recognized prerequisite for data disclosure, it remains underexplored in the emerging Metaverse. This environment, characterized by highly intrusive virtual reality (VR) and extended reality (XR) technology that collect vast amounts of heterogenous data, significantly amplifies privacy concerns. This master’s thesis investigates the influence of trust on privacy decisions within this context. A two-step methodological approach was employed, combining a systematic literature review with an exploratory qualitative study using user interviews. The findings reveal that user trust is highly dependent on the context of use, distinguishing between low-stakes and high-stake usage contexts. Additionally, the provider’s country of origin emerged as a significant antecedent of trust. Finally, the study demonstrated that for providers to build and maintain trust, they must actively implement effective strategies, like increasing user control and adopting more transparent privacy practices.
Keywords: trust, privacy, Metaverse, virtual reality, extended reality, privacy decisions, privacy concerns